Visceral Leishmaniasis with Renal Involvement: A Case Report (Journal of Nobel Medical College, 2024)
Visceral leishmaniasis (VL) is widespread in tropical and temperate region. It is caused by the protozoan parasite leishmania species and is transmitted through the bite of infected female sandflies. It manifests as pancytopenia, hepatosplenomegaly and fever. Here, we present a case of 20-year-old male presented with difficulty in swallowing for 2 months, abdominal distention for 30 days and shortness of breath for 20 days along with progressive renal impairment. Clinical examination revealed hepatosplenomegaly and laboratory investigations confirmed pancytopenia, nephrotic range proteinuria, hematuria and hypocomplementemia. Bone marrow aspiration and biopsy was performed which showed leishmania donovani (LD) bodies. It’suncommon presentation makes it challenging for physicians as well as pathologist to make a timely diagnosis.